Syphilis in heterosexual women: case characteristics and risk factors for recent syphilis infection in Tokyo, Japan, 2017–2018. (November 2020) - Nishiki, Shingo; Arima, Yuzo; Yamagishi, Takuya; Hamada, Takashi; Takahashi, Takuri; Sunagawa, Tomimasa; Matsui, Tamano; Oishi, Kazunori; Ohnishi, Makoto
In response to an increase in heterosexual syphilis notifications in Tokyo, we conducted a questionnaire-based case–control study among women aged ≥20 years and sexually active in the past six months who sought a syphilis test in Tokyo during 2017–2018. Cases were women diagnosed as recent syphilis infection based on serological tests. Controls were serologically non-reactive or those with only a past syphilis infection. We described cases and assessed for risk factors of recent syphilis using logistic regression. A total of 524 women (60 cases, 464 controls) were enrolled. Notably, among cases, 10 (16.7%) were students, 3 (5.0%) had a history of syphilis, and 14 (23.3%) had a single sex partner in the past six months. Female sex worker (FSW) status was strongly associated with syphilis (odds ratio [OR] = 3.40; 95% confidence interval [CI] = 1.96–5.90). In multivariable analysis, recent syphilis was associated with inconsistent condom use for vaginal/anal sex among FSWs (adjusted OR [aOR] = 3.42; 95%CI = 0.92–12.70) and among non-FSWs, with younger age (aOR = 0.36; 95%CI = 0.19–0.70; increase per category from 20–24, 25–29 to ≥30 years) and ≤high school education (aOR = 5.24; 95%CI = 1.95–14.10). A notable proportion of cases were those with first time infection and those with only a single partner. Moreover, risk factors differed between FSWs and non-FSWs, and a multi-pronged approach to prevent syphilis is required.